Ribosome deficiency induces Salmonella filamentation within host cells - Zhihui Lyu; Cierra Wilson; Kalyn Weiss; Spencer Lewis; Kurt Fredrick; William Margolin; Jiqiang Ling (mBio)
ABSTRACT The ribosome is the central hub for protein synthesis and is heavily targeted by antibiotics. Ribosomal mutations, antibiotic treatment, and nutrient starvation can alter translational efficiency and lead to stressed cells. Ribosome deficiency plays a critical role in stress responses and disease progression; yet, how it affects bacteria-host interactions remains poorly understood. In this study, we show that a ribosome-deficient strain exhibits a surprising morphological change from rod shape to filamentous in Salmonella cells growing inside host macrophages. Such filamentation depends on an acidic condition within macrophages and in a defined medium mimicking macrophage conditions. Further genetic analyses revealed that filamentation of the ribosome-deficient strain depends on overexpression of hisH, a gene involved in histidine biosynthesis. Transcription of the histidine biosynthesis operon is regulated by a small leader peptide HisL. Slow translation of HisL in the mutant strain activates transcription of the histidine operon and induces filamentation. In support of this model, we show that ribosome inhibitors also increase the expression of the histidine operon and cause filamentation in wild-type Salmonella. Bacterial filamentation has been implicated as an adaptive strategy. We show that filamentation improves the survival of Salmonella cells under acid stress, and filamentous cells resume normal division after the acid stress is removed. Our work thus demonstrates that ribosome deficiency caused by mutations and antibiotics induces Salmonella filamentation in host cells as a potential survival strategy.IMPORTANCEBacteria growing inside host cells encounter various stresses and have evolved multiple adaptive mechanisms. One such mechanism is morphological changes, such as from rod-shaped cells to filaments. Salmonella is a rod-shaped pathogen that infects over 100 million people each year as well as numerous farmed animals. In this work, we present new findings that slowing down protein synthesis causes Salmonella to filament inside mammalian host cells. Combining genetic, molecular, and cell biology approaches, we demonstrate that filamentation of Salmonella cells is caused by translational and transcriptional regulation of the histidine operon. Filamentous cells appear to tolerate acid stress better and resume cell division after the stress is removed. This work highlights intriguing translational control of bacterial cell division and morphology, which may facilitate Salmonella cells to adapt to the host environment.